Tingkat ketransitifan verba bahasa Lamaholot dialek Ritaebang - Frederikus Paulino Moso Niron (UPT P2M Politeknik Negeri Malang, 2019)
The tittle of this research is Transitivity Verb Rate in Lamaholot Language Ritaebang Dialect which conducts to answer a language phenomenon and the objective of this research is to describe: (1) the types of verb in Lamaholot language, (2) the parameters of BLDR transitivity verb, (3) BLDR valence verb change strategy. Descriptive qualitative method used to describe the language phenomenon. This phenomenon conducted in West Solor Urban-Village, West Solor Sub-District, East Flores Regency, and East Nusa Tenggara Province. There were some methods used in this research, such as: observing method; (a) sadap-libat-cakap, (b) take notes, (c) recording and transcribing. Based on language phenomenon, the theories can be considered appropriate to be applied such as Generative Theory, Lexical Functional Grammar (LFG), and Transitivity Theory of Hopper and Thompson (1982). The result of the data indicated BLDR verb consist of intransitive verb that have grammatical function such as SUBJ (enclitic), transitive verb has grammatical function such as SUBJ and OBJ, and ditransitive verb have grammatical function such as SUBJ, OBJ, and OBJ2. Based on the analysis, the rate of BLDR transitivity verb has high transitivity. Seven of ten transitive clauses had plus score for parameter aspect, relationship of patient, polarity, modality, agent capacity, patient individuality, participant, kinetic, and intentional. Meanwhile, there are three verbs of punctuality parameters had negative score. The last research was about BLDR valence change strategy, it intended that in BLDR, the valence change strategy affected ups and down transitivity degree of a verb through enclitic process and connection of verb causality.